2015
DOI: 10.1063/1.4927447
|View full text |Cite
|
Sign up to set email alerts
|

Standing jumps in shallow granular flows down smooth inclines

Abstract: The shapes of standing jumps formed in shallow granular flows down an inclined smooth-based chute are analysed in detail, by varying both the slope and mass discharge. Laboratory tests and analytic jump solutions highlight two important transitions. First, for dense flows at high mass discharge, we observe a transition between steep jumps and more diffuse jumps. The traditional shallow-water equation offers a valid prediction for the thickness of the steep water-like jumps. Diffuse frictional jumps require a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 24 publications
7
78
1
Order By: Relevance
“…For the unsteady flows with θ > 30 • , deposition is only possible via the upslope traveling jump, where particles flow along the slope to the traveling jump and are deposited on the face of the jump. Previous studies of dry granular flows in a chute indicate that a minimum base incline angle and a downstream obstacle are required for the formation of the jump [41,42,44], as mentioned previously. Here, increased θ due to cohesion and the presence of the downstream bounding walls satisfy these two conditions, respectively.…”
Section: Transition To Unsteady Flowssupporting
confidence: 54%
“…For the unsteady flows with θ > 30 • , deposition is only possible via the upslope traveling jump, where particles flow along the slope to the traveling jump and are deposited on the face of the jump. Previous studies of dry granular flows in a chute indicate that a minimum base incline angle and a downstream obstacle are required for the formation of the jump [41,42,44], as mentioned previously. Here, increased θ due to cohesion and the presence of the downstream bounding walls satisfy these two conditions, respectively.…”
Section: Transition To Unsteady Flowssupporting
confidence: 54%
“…In several CDR flows, MTI plots show triangular shaped features at specific ranges (Figure h). We interpret these features as standing waves or shocks (Gray et al, ; Faug et al, ) or even jets (Hákonardóttir et al, ), perhaps initiated by obstructions and terrain features such as changing roughness, slope (Hopfinger, ), or narrowing width of the couloir. Standing shocks occur when the flow is supercritical; that is, the Froude number is greater than 1, so that their existence is dependent on flow height and velocity.…”
Section: Avalanche Flow Regimesmentioning
confidence: 99%
“…In the momentum equation, assuming that the jump volume shrinks into a singular surface ( ∼ 0) yields S = 0. In other words, the volume and surface forces acting over the finite length of the jump are neglected here, though a recent experimental study dedicated to standing jumps formed in granular flows revealed the importance of those forces under certain circumstances when the jumps become diffuse [4]. This crucial assumption will be further discussed while concluding the present paper.…”
Section: Simple Description Of the Granular Borementioning
confidence: 93%
“…The density of the granular fluid is ρ P φ, where ρ P is the particle density. A detailed discussion on considering values of k and β slightly different from 1 (either upstream or downstream the shock) is given in [1,4] and some other references therein. In the momentum equation, assuming that the jump volume shrinks into a singular surface ( ∼ 0) yields S = 0.…”
Section: Simple Description Of the Granular Borementioning
confidence: 99%
See 1 more Smart Citation